Serious life events and the risk of latent autoimmune diabetes in adults (LADA) and Type 2 diabetes. Issue 9 (12th July 2017) - Rasouli, B.; Andersson, T.; Carlsson, P.‐O.; Hjort, R.; Löfvenborg, J. E.; Martinell, M.; Groop, L.; Tuomi, T.; Carlsson, S.
Abstract: Aim: It has been suggested that experiencing serious life events may promote Type 1 diabetes in children. Studies in adults are lacking, as are studies on the interaction of life events with genetic factors. We aimed to investigate life events and the risk of latent autoimmune diabetes in adults (LADA) and Type 2 diabetes while taking into account HLA genotype. Methods: Analysis was based on 425 incident cases of LADA, 1417 incident cases of Type 2 diabetes and 1702 population‐based controls recruited in Sweden between 2010 and 2016. Self‐reported information on life events including conflicts, divorce, illness/accidents, death and financial problems experienced during the 5 years preceding diagnosis/index year was used. Odds ratios (ORs) and 95% confidence intervals (95% CI) were calculated by logistic regression and adjusted for age, sex, BMI, family history of diabetes, smoking, physical activity and education. Results: Overall there was no association between experience of any life event and either LADA (OR 0.86, 95% CI 0.68–1.08) or Type 2 diabetes (OR 1.00, 95% CI 0.83–1.21). The results were similar for individual events as well as in separate analysis of men and women. Similar results were seen in more autoimmune LADA (glutamic acid decarboxylase antibodies > median) [OR (any life event) 0.88, 95% CI 0.64–1.21] and in LADA carriers of the high‐risk HLA DR4‐DQ8 genotype (OR 0.89, 95% CI 0.61–1.29). Conclusions: Our findings indicate that experience of a serious life event, including the death of a family member, divorce or financial problems, is not associated with an increased risk of LADA, overall or in genetically susceptible individuals. What's new?: Experience of a serious life event has been linked to Type 1 diabetes in children but studies in adults are scarce. The results indicate that experience of serious life events does not increase the risk of latent autoimmune diabetes in adults or Type 2 diabetes. Findings were consistent for men and women, and in carriers of the high‐risk HLA genotype DR4‐DQ8 . Psychosocial factors seem to be less important for onset of diabetes in adults than in children.